Digital Identity As A Basis For A New Economic Model - Babayeva Sabinabonu Davronbek qizi (Genius Journals, 2025)
This article explores digital identity as a fundamental component of the emerging economic model. Beyond the technical dimensions, the study delves into institutional, social, and economic impacts of digital identification systems. Special attention is given to how digital identity fosters new mechanisms of trust, reshapes market interactions, and underpins digital platforms, remote employment, online banking, and e-government services. The paper analyzes international practices from Estonia, India, Singapore, Finland, and South Korea, while addressing challenges related to privacy, digital inequality, and algorithmic governance. The author argues for a balanced approach that combines technological innovation with ethical and legal safeguards to ensure an inclusive and trustworthy digital economy
Keywords: Digital identity; digital transformation; trust; decentralization